Out Lag Synchronization of Fractional Order Delayed Complex Networks with Coupling Delay via Pinning Control - Weiwei Zhang; Jinde Cao; Dingyuan Chen; Ahmed Alsaedi (Complexity)
This paper discusses the out lag synchronization of fractional order complex networks (FOCN) including both internal delay and coupling delay and with the employment of pinning control scheme. Using comparison theorem and constructing the auxiliary function, several synchronization criterions by linear feedback pinning control are presented. The model and the obtained results in this work are more general than the previous works. Correctness and effectiveness of the theoretical results are validated through numerical simulations.